Delivering Blue-Green Infrastructure: Innovation Pathways for Integrating Multiple Values - Kuitert, Lizet; van Buuren, Arwin (Frontiers in Sustainable Cities, 2022)
Realizing a multifunctional blue-green infrastructure (BGI) as a nature-based solution for the urban water system and built environment within crowded city areas is seen as a promising route for the process of climate adaptation. BGI projects like rain gardens, green roofs, and water squares can be combined to achieve a variety of technical (drainage), environmental (biodiversity), economic (property development) and social (health and wellbeing) goals and values at a local neighborhood level. As integrating such values within local governments' existing fragmented structures and procedures has proved to be challenging, urban governments are increasingly experimenting with innovative governance approaches at different levels to capitalize on the multiple benefits of BGI. Nevertheless, policy actors who try to justify their choices in the face of value conflicts are both constrained and enabled by the institutions they can call on. Using a qualitative comparative case study, this article therefore aims to gain insight into different ways of, or approaches to, organizing value integration. In particular, we compare: (1) a top-down case of programmatic steering to translate value integration into a neighborhood approach; (2) a market-oriented innovative procurement approach to local public-private partnership projects; and (3) a case of invitational governance for a future-proof neighborhood that is striving for a sense of citizen ownership. Our findings demonstrate the conditions, drivers, and barriers to the value integration of different governance innovations in relation to time-related issues, the types of support available, organizational embedding, and stakeholder involvement. Our specific focus is on understanding how social and sustainability and spatial and technical values are integrated. This paper thus helps us to get to grips with different pathways to value integration in the context of urban infrastructures, as well as their applicability and the conditions for success. These insights will enable the further strengthening of our capacity to build climate-proof cities in a value-driven and integrative manner.